Lifestyle Phenomena Of South Kalimantan Communities That Contribute To Stroke Incidents : Mixed Method Research - Oktovin, Oktovin; Er Unja, Ermeisi (Sean Institute, 2022)
Stroke incidence in South Kalimantan ranks 6th out of 34 provinces in Indonesia. The incidence of stroke in this province continues to increase every year. In 2016 the stroke rate reached 739 cases; in 2018, it increased to 9,361 stroke cases in 13 districts in South Kalimantan. The purpose of this study is to identify in detail the description of the lifestyle of the people in South Kalimantan. The research design is Mixed Method with The Explanatory Sequential Design model. Quantitative research samples totaling 426 samples spread across 13 districts in South Kalimantan were selected with the Probability Sampling technique with the type of Stratified Random Sampling. Qualitative data collection involved 10 participants from 6 districts in South Kalimantan. The majority of respondents in this study were aged 36-45 years (32.9%), male (52.6%), worked as office workers (39%), and had a tertiary level of education (48.8%). The people of South Kalimantan have a habit of consuming foods high in sodium and fat (90.8%), moderate activity patterns (62.0%), the majority are light smokers (25.4%), and those who consume alcohol (16.7%), stress category mild (39.9%), and low health control at the nearest health facility (68.8%). The living habits of the people in South Kalimantan are still low health, where eating habits are high in sodium and fat, low daily physical activity, smoking and consuming alcohol, stress, and low routine check-ups at the nearest health facility. This is because the pattern that has been followed has become a habit since childhood. Community knowledge and obedience are also originators of the bad habits of people's days